A statistical framework for identifying past PRDM9 binding targets in primates - Tumian, Afidalina; Myers, Simon (2014)
Recombination is a basic biological force, which, with mutation, plays an important role in generating new combinations of alleles in each chromosome, by shuffling and exchanging genetic material between maternal and paternal chromosomes. Multiple lines of evidence suggest that the rapidly evolving zinc-finger (ZF) protein, PRDM9, is responsible for initiating much or all of recombination in human. PRDM9 shows extreme variation in both the number and sequence of its ZFs, between species and amongst individuals, across mammals. The rapid evolution of the PRDM9 ZF array may be a response to escape a self-destructive drive called biased gene conversion, which can cause preferential transmission of hotspot disrupting alleles, and leading to erosion of vital recombination sites – and hotspot signaling motifs – in the genome through time. This research attempts to uncover ancestral PRDM9 binding targets in humans and primates. By using six primate genomes, this work involves the development of statistical methods that identifies the locations where meiotic recombination could have occurred in the past. This is achieved by looking for short words that have undergone rapid losses or gains in each lineage. As a result, we found many short and different words across lineages. In conclusion, our findings imply a rapidly evolving mechanism landscape of past PRDM9 binding targets.